Increase in cyclooxygenase‐2 (COX‐2) expression in keratinocytes and dermal fibroblasts in photoaged skin. (September 2014) - Surowiak, Pawel; Gansukh, Tserenchunt; Donizy, Piotr; Halon, Agnieszka; Rybak, Zbigniew
Summary Background Interleukins and NFκ‐B are involved in the development of inflammatory reactions. It has been suggested that these proteins are important contributing factors in the process of photoaging of skin. Moreover, interleukins and NFκ‐B are known to be capable of inducing expression of cyclooxygenase 2 (COX‐2). Expression of COX‐2 in various populations of skin cells has not been examined in the specific processes of aging. Objectives The study aimed at evaluating COX‐2 expression in skin samples originating from patients with chronologically aged and photoaged skin at various stages of skin aging. Methods Immunohistochemical analysis of COX‐2 reactivity was conducted on samples originating from 52 women undergoing surgery for reasons other than skin pathology. Results Our study demonstrated that COX‐2 expression in keratinocytes and fibroblasts was significantly higher in skin samples affected by photoaging than in samples affected by endogenous aging or obtained from younger individuals. Conclusions The results indicate that COX‐2 may be involved in the pathogenesis of the photoaging process. Inhibition of expression or activity of the enzyme may find application in photoaging treatment and/or prophylaxis.